Nd Evaluation And Suitability of Land For Development of Sorghum (Sorghum bicholor L.) on Peat Land in West Sumatera, Indonesia - Juniarti, Juniarti; N, Sandi.; A, Sari.; A , Agustar.; D.P, Sari. (Faculty of Agriculture, Universitas Malikussaleh, 2025)
Sorghum is a perennial food crop that has great potential for development in Indonesia. The development of sorghum will increase land productivity, supporting the development of sustainable agriculture and enhancing Indonesian food production. The research findings establish sorghum as an ideal choice for enhancing the productivity of arid, acidic, or otherwise unproductive lands, including former mining areas reclaimed. Through the assessment of land characteristics suitable for sorghum development as biomass energy crop in West Sumatra, Indonesia, this research endeavors to facilitate the sustainable growth of sorghum cultivation within the region. This research aims to evaluate the suitability of land for sorghum in West Sumatra, Indonesia. Regency uses purposive sampling and survey methods. The results showed that peatland in West Sumatera, Indonesia has potential for the development of sorghum plants with average temperature characteristics 25-27 º C, rainfall <200 mm, air humidity <75%, good drainage, soil depth of peatland > 60 cm, pH 4.4 - 5.1 but low N, P and K nutrient availability. Key words: land evaluation, perennial crop, marginal land